Changes in Post Traumatic Stress Symptoms Among Women in Substance Use Disorder Treatment: The Mediating Role of Bodily Dissociation and Emotion Regulation. (January 2013) - Price, Cynthia J.; Herting, Jerald R.
Individuals in substance use disorder (SUD) treatment have shown high levels of difficulty with emotion regulation, as well as a high prevalence of reported trauma and symptoms of post-traumatic stress (PTS). Dissociation from the body is a common clinical experience among women with a history of sexual trauma. Research has shown promising effects of mind-body approaches in SUD treatment, as well as the importance of emotional regulation in conceptual models of psychopathology. The current study examines the mediating role of bodily dissociation and emotion regulation on PTS symptoms in a sample of women enrolled in substance use disorder treatment. Results indicate that bodily dissociation and emotion regulation had significant direct effects on PTS symptoms from baseline to a 6-month follow-up, and that bodily dissociation also may indirectly operate to reduce PTS symptoms through its effect on emotion regulation difficulties. These results suggest the importance of addressing bodily dissociation and emotion regulation difficulties in women's substance use disorder treatment.